Correlation of capacitance and actuation in ionomeric polymer transducers - Akle, B. J. (2005)
Ionomeric polymer transducers are electromechanical actuators fabricated from ion-exchange membranes that have been surface plated with conductive metal. In this paper we discuss a series of experiments that characterize the electromechanical actuation response of three families of ionomers: Nafion (a product of DuPont), BPSH (sulfonated poly(arylene ether sulfone)) and PATS (poly(arylene thioether sulfone)). The first polymer is commercially-available while the second and third polymers are synthesized by the direct polymerization of sulfonated monomers in our lab. The mechanical properties and actuation response of Nafion-117, BPSH, and PATS of varying ionic content are studied in the Lithium cation form. The strain response of the materials varies from 50 μ strain/V to 750 μ strain/V at 1Hz. A linear correlation was found between the strain response and the capacitance of the material. This correlation was independent of the polymer composition and the plating parameters. All of the ionomers analyzed in this work exhibited a strain-to-charge response between 9 μstrainCm2μstrainCm2 and 15 μstrainCm2μstrainCm2. Due to the fact that the low-frequency capacitance of an ionomer is strongly related to charge accumulation at the blocking electrodes, this correlation suggests a strong relationship between surface charge accumulation and mechanical deformation in ionomeric actuators.